High quality factor confined Tamm modes - C. Symonds (Nature Portfolio, 2017)
Abstract We demonstrate that quality factors up to 5000 can be obtained in Tamm-like hybrid metal/semiconductor structures. To do this, a Bragg mirror is covered by a thin transparent layer and a metallic film. The reduced losses of these modes are related to an intermediate behavior between conventional Tamm plasmon and Bragg modes lying deeper in the semiconductor medium. One of the most striking features of this approach is that these super Tamm modes can still be spatially confined with the metal. Confinement on micrometric scale is experimentally demonstrated. The simplicity and versatility of high-Q mode control by metal structuration open perspectives for lasing and polaritonic applications.